2019
DOI: 10.1016/j.rbms.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Being questioned as parents: An interview study with Swedish commissioning parents using transnational surrogacy

Abstract: This study sought to explore how Swedish parents who had commissioned surrogacy abroad experienced the process of parenthood recognition. The study consisted of in-depth interviews with five couples and 10 individuals representing 10 additional couples who had used surrogacy abroad, mainly in India. The construction of motherhood and fatherhood in the Swedish system contradicts how parenthood is defined in the surrogacy process. This study found that the formal recognition of parenthood involved a complex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…It is the social work profession that bears the brunt of ill-designed policies that they have to implement. As we saw with Arvidsson et al (2018a, b) as well as our own study, it is individual social workers who are the face of a system that seems to be wilfully denying the reality of the relationships in surrogacy and forcing people into categories they do not belong to. Change that is informed by the experiences of members of surrogacy arrangements and the social workers who interact with them is overdue.…”
Section: Limitations and Future Directionsmentioning
confidence: 81%
See 1 more Smart Citation
“…It is the social work profession that bears the brunt of ill-designed policies that they have to implement. As we saw with Arvidsson et al (2018a, b) as well as our own study, it is individual social workers who are the face of a system that seems to be wilfully denying the reality of the relationships in surrogacy and forcing people into categories they do not belong to. Change that is informed by the experiences of members of surrogacy arrangements and the social workers who interact with them is overdue.…”
Section: Limitations and Future Directionsmentioning
confidence: 81%
“…A Swedish study by Arvidsson et al (2018b) found that social workers are uncertain about their role, given the absence of legal guidance, and that they wrestle with ethical questions relating to informed consent as well as the sometimes conflicting interests of the surrogate and child. In another study, Arvidsson et al (2018a) found that intended parents were affected quite profoundly by a process they experienced as protracted and unsuitable, despite social workers' efforts to make the system work for their clients. However, the Swedish system is not similar to that of the UK or New Zealand so it is difficult to make detailed comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…thirteen on Indian ( 19–31 ), nine on the US ( 32–40 ), and five articles on the Israeli context ( 36 , 41–44 ). The least studied country contexts in this sample include Greece ( 45 ), Iran ( 46 ), Italy ( 47 ), Mexico ( 48 , 49 ), Norway ( 50 ), Sweden ( 51 , 52 ), and Russia/Ukraine ( 53 , 54 ). In countries where surrogacy is not legal, only intended parents through transnational surrogacy have been interviewed (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, joint adoption has been very difficult to achieve for same-sex couples (Malmquist & Sp˚anberg Ekholm, 2020), and because lesbian couples gained access to fertility treatment with donated sperm in 2005, fewer lesbian couples are willing to engage in shared parenting with gay men (Malmquist, 2016). At present, gay men generally face formidable obstacles when trying to start a family (Andreasson & Johansson, 2017;Arvidsson, Johnsdotter, Emmelin, & Ess en, 2019;Malmquist & Sp˚anberg Ekholm, 2020).…”
Section: Gay Fatherhood In Swedenmentioning
confidence: 99%
“…Surrogacy arrangements are not allowed within Swedish healthcare (SOU 2016:11), but there are agencies that help couples and singles to carry out surrogacy pregnancies abroad. India was a common destination before that country banned foreign couples' surrogacy (Arvidsson et al, 2019;Sydsj€ o, Skoog Svanberg, & Lampic, 2019). Currently, most Swedish gay couples turn to clinics in the United States.…”
Section: Gay Fatherhood In Swedenmentioning
confidence: 99%